EDUKASI PENCEGAHAN PENYALAHGUNAAN NAPZA BAGI SISWA SMAN 4 KONAWE SELATAN - Wa Ode Sitti Zubaydah; Nur Illiyyin Akib; Hasnawati Hasnawati; Lade Aburifal Basri; Amina Amina; Ana Aprilia Azzahrah; Annisa Rizki; Annisa Purnama Sari; Andini Risky Khaerunnisa Silondae; Andi Rafita Ayu Risky Utami; Suci Wahyuni (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Drug abuse involving Narcotics, Psychotropics, and Other Addictive Substances (NAPZA) poses a serious threat to the physical and mental health as well as the future of young generations. Adolescents, as a vulnerable group, require systematic and sustainable educational interventions to enhance their knowledge and awareness of the risks and consequences of drug abuse. This community service activity aimed to improve students’ understanding of the types, risk factors, and impacts of NAPZA abuse through participatory health education. The implementation method consisted of preparation, inter-institutional collaboration, human resource readiness, and educational activities including pretest, material delivery through lectures and discussions, brief consultations, and posttest evaluation. The activity involved 35 students of SMAN 4 Konawe Selatan and was conducted by students of the Pharmacist Professional Education Program, Universitas Halu Oleo, in collaboration with the South Konawe District Health Office. The evaluation results demonstrated a significant improvement in students’ knowledge levels, with the proportion of students in the good knowledge category increasing from 42.86% before the intervention to 71.43% after the intervention, while the poor knowledge category decreased to 8.57%. These findings indicate that health education on NAPZA is effective in enhancing students’ knowledge and awareness of the dangers of drug abuse. This program is expected to serve as a sustainable collaboration model between educational institutions and health authorities in promoting preventive efforts against drug abuse among adolescents.